An approach for identifying and analysing reference features and spatial relations used in mountain emergency calls - Bunel, Mattia; Duchêne, Cécile; Olteanu-Raimond, Ana-Maria; Villanova-Oliver, Marlène; Bonhoure, Grégoire; Jouan, Tiphaine (Proceedings of the ICA, 2019)
The CHOUCAS project aims at helping mountain rescue services to locate a victim who describes her location by means of spatial relations with reference geographic features. In this context, the study presented in this paper aims at better understanding what reference features and spatial relations are used to locate oneself in a mountain area, with the ultimate aim of designing tools to help the rescuers. Audio tapes of real emergency calls were used as starting material. The core of the work is the design of a template to transcribe the location information contained in these calls while structuring it. A first analysis of the transcribed calls shows that projective or directional static spatial relations are the most used, and that a finer classification of reference features and spatial relations is needed. In order to synthetically present the location information contained in a call, an additional representation by means of a sketch map with a dedicated symbolisation is proposed.